Conservation of Prion-Like Composition and Sequence in Prion-Formers and Prion-Like Proteins of Saccharomyces cerevisiae - Ting-Yi Su; Paul M. Harrison (Frontiers in Molecular Biosciences, 2019)
Prions in eukaryotes have been linked to diseases, evolutionary capacitance, large-scale genetic control, and long-term memory formation. Prion formation and propagation have been studied extensively in the budding yeast Saccharomyces cerevisiae. Here, we have analysed the conservation of sequence and of prion-like composition for prion-forming proteins and for other prion-like proteins from S. cerevisiae, across three evolutionary levels. We discover that prion-like status is well-conserved for about half the set of prion-formers at the Saccharomycetes level, and that prion-forming domains evolve more quickly as sequences than other prion-like domains do. Such increased mutation rates may be linked to the acquisition of functional roles for prion-forming domains during the evolutionary epoch of Saccharomycetes. Domain scores for prion-like composition in S. cerevisiae are strongly correlated with scores for such composition weighted evolutionarily over the dozens of fungal species examined, indicating conservation of such prion-like status. Examples of notable prion-like proteins that are highly conserved both in sequence and prion-like composition are discussed.